The fight against malware as a service. Issue 8 (August 2021) - Davidson, Ron
Abstract : Malware developers and distributors wasted no time in exploiting the Covid-19 pandemic for their own malicious objectives. In 2020, the number of new malware samples nearly doubled compared with 2019. 1 More concerningly, cyber criminals are also becoming smarter. Rather than merely relying upon a larger quantity of threats, they are also leveraging technology innovations to grow their criminal organisations and generate new revenue streams.